Consumption Behaviours in the Market of Tourist Services. Motivations and Needs for Holiday Trips of Tourism and Recreation Students - Blanka Gosik (Ekonomiczne Problemy Turystyki, 2016)
The aim of this article is to identify students’ holiday trips. Particular attention is paid to the issue of needs, motives and tourist behaviours of this social group. Students as a specific community due to limited financial resources, while having a relatively large amount of free time, are an important market segment of tourist trips. Recognition of this specificity is important both for the people involved in the organization of tourism, as well as those providing services necessary for the operation of tourism.